External Mechanical Microstimuli Modulate the Osseointegration of Titanium Implants in Rat Tibiae. (3rd December 2013) - Zacchetti, Giovanna; Wiskott, Anselm; Cugnoni, Joël; Botsis, John; Ammann, Patrick
Abstract : Purpose . To assess the effect of external mechanical microstimuli of controlled magnitude on the microarchitecture of the peri-implant bone beds in rat tibiae. Materials and Methods . Tibiae of forty rats were fitted with two transcutaneous titanium cylinders. After healing, the implants were loaded to 1 to 3 N, five days/week for four weeks. These force levels translated into intraosseous strains of 700 ± 200  μ ε, 1400 ± 400  μ ε, and 2100 ± 600  μ ε . After sacrifice, the implants' pullout strength was assessed. Second, the bone's microarchitecture was analyzed by microcomputed tomography (μ CT) in three discrete regions of interest (ROIs). Third, the effect of loading on bone material properties was determined by nanoindentation. Results . The trabecular BV/TV significantly increased in an ROI of 0.98 mm away from the test implant in the 1 N versus the 3 N group with an opposite trend for cortical thickness. Pull-out strength significantly increased in the 2 N relatively to the nonstimulated group. Higher values of E-modulus and hardness were observed in the trabecular bone of the 2 N group. Conclusion . The in vivo mechanical loading of implants induces load-dependent modifications in bone microarchitecture and bone material properties in rat tibiae. In pull-out strength measurements, implant osseointegration was maximized at 2 N ( 1400 ± 400  μ ε ) .